(untitled) (Heritage, 2020)
The paper will present and analytically-sinthetically analyze Teodosije’s hagiography of Peter of Korisha in the light of hermetic tradition. The center of research is the character of Saint Peter of Kornisha in the hermetic tradition of medieval literature, the duality of his nature and importance of struggle he takes on, going towards deification. In order to present the struggle of Saint Peter of Korisha in accordance with the spiritual, literary and psychological foundations, special attention will be paid to the correlation possibilities of reading medieval literature and literature of the 19th and 20th centuries. The combination of the miraculous and the realistic, as a feature of Teodosije’s poetics, leads to the understanding of the Hagiography of Peter of Korisha outside the given framework of the old Serbian literature.